Cognitive and Social Influences of Social Media: Examining the Effects of Big Five Personality Traits of Students at Secondary Level - Sehrish Sarfaraz; Hina Shoukat; Nadia Shaheen; Wajid Mahnaz (Social Science Review Archives, 2025)
The Big Five Personality Traits—openness, conscientiousness, extraversion, agreeableness, and neuroticism—are widely regarded as a comprehensive framework for understanding individual differences. These traits influence various behaviors, including social interactions, learning preferences, and technology adoption. Objectives of the study were; 1) To analyze the usage of Social Network Sites by the students for educational purposes. 2) To investigate the association between social network site preference and Big Five Personality Traits of students. 3) To explore the role of social network sites in social development of students. All 8617 Students of grade 10th of District Attock, (4,868 Boys & 3,749 Girls) at secondary and higher secondary school level in 248 public schools were the population of the study. 816 students were the sample for this study from the population. Proportional Sampling technique was used for sampling. Big Five Personality Tool consists of 39, Usage of Social Network Sites tool consists of twenty nine different items for five basic and commonly used Social Network Sites. Reliability of the tools was found by using Cronbach’s Alpha. For content validity, both research tools were validated from the experts of field of education while for construct validity, EFA was performed. The findings indicate a significant positive correlation (r = .452, p < .01) between social network site usage and their use for educational purposes. This suggests that increased engagement with social network sites is moderately associated with utilizing them for academic-related activities. Hence, it is recommended to integrate social networking platforms into formal educational settings by developing guidelines for their academic use. Teachers and administrators should promote the use of SNS for collaborative learning, resource sharing, and academic discussions.